PMMA (polymethyl methacrylate) composite glass material as well as preparation method and application thereof
By using the condensation reaction between the phosphate group-containing compounds and inorganic glass in the PMMA material to form Si-O-P chemical bonding, the problem of the reduction of light transmittance when the surface hardness is improved is solved, and the coordinated improvement of hardness and light transmittance is achieved, and a PMMA composite glass material with high wear resistance and extremely high reliability is obtained.
Patent Information
- Application Number
- CN202411997990.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
While the existing PMMA materials improve surface hardness, the light transmittance is significantly reduced, making it difficult to improve surface hardness while retaining high transparency to increase the wear resistance of the material.
By placing the liquid matrix material and inorganic glass between two inorganic glasses, the polymerization reaction is carried out by heating, and the condensation reaction between the phosphoric acid group-containing compound and the contact surface of the inorganic glass is formed to form a chemical bond of Si-O-P, thereby forming a polymerization layer that is difficult to separate between the inorganic glasses, thereby improving the surface hardness of the PMMA material.
The Mohs hardness of the surface of PMMA composite glass material has been greatly increased from 2.5 to 6, and the light transmittance can be as high as 92%, breaking the balance limit between hardness and light transmittance, and obtaining a PMMA composite glass material with high wear resistance and extremely high reliability.
Smart Images

Figure CN119795701A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic glass materials, and in particular to a PMMA composite glass material and a preparation method and application thereof. Background Art
[0002] Transparent polymer materials represented by polymethyl methacrylate (PMMA) have attracted widespread attention from academia and industry due to their relatively excellent strength and toughness in overall physical properties. They have been successfully applied in many key fields, such as rail transportation, aerospace, electronic communications, and medical devices. Although PMMA materials have outstanding application advantages in the above fields due to their easy molding, good functional expansion, and high optical transmission, they have the disadvantage of low surface hardness, which limits their durability. Relevant research data show that there has been an urgent expectation for PMMA materials with high-hardness surfaces in the field of engineering applications, especially on the basis of retaining their high transparency, there is a strong demand to increase the surface hardness to increase the wear resistance and reliability of the material.
[0003] However, in order to improve the surface hardness of PMMA materials, a common solution in the prior art is to add inorganic fillers. For example, silicon dioxide, titanium dioxide, aluminum oxide, silicon carbide, silicon nitride, zirconium dioxide, etc. with micron or nanometer particle size are added, and first prepared into an oily dispersion system and then introduced. However, no matter which inorganic filler is used, while improving the hardness of PMMA materials, it will inevitably cause a significant decrease in light transmittance, and even the transparency almost no longer exists. In addition, there is also a method of using surface coating to achieve surface hardness improvement. For example, CN117229555A discloses a method for preparing a surface hardening layer of a resin-based material and its composite material. The surface of a plastic (including engineering plastics), plastic, and a composite material formed by an organic resin as a substrate and an inorganic material, a fiber material, etc. is made into a coating or coating to improve its hardness. Specifically, the preparation method of the hardened coating includes but is not limited to: vacuum evaporation, sputtering coating, arc plasma in physical vapor deposition (PVD) technology. One, two or more of bulk plating, ion plating, and molecular beam epitaxy, microwave plasma CVD (MPCVD), DC plasma CVD, hot wire CVD (HFCVD), combustion flame CVD (CFCVD) in chemical vapor deposition (CVD) technology, chemical plating, electroplating, etc.; one, two or more of the methods and processes for making hardened coatings, including but not limited to powder spraying, electrostatic spraying, pressure spraying, rotary spraying, roller coating, scraping, curtain coating, mold forming, etc. In the above methods, if it is necessary to retain relatively high transparency, the thickness of the surface modification layer is extremely thin at the nanometer level. Common collisions and wiping between objects, or hardness indentation testing processes can cause the functional layer to rupture and fail, and the wear resistance stability is still low; if the thickness of the surface modification layer further reaches the micrometer level, the transparency is basically completely lost.
[0004] CN110218433A discloses a glass-like polymer composite material and a preparation method thereof, comprising the following components in weight percentage: PC 30%-60%, PMMA 30%-50%, compatibilizer 0%-10%, toughening agent 3%-8%, inorganic nanoparticles 1%-10%, UV stabilizer 0.1%-1%, lubricant 0.5%-2%, antioxidant 0.1%-0.5% and carbon black 1%-3%. The glass-like polymer material obtained by the above method has good mechanical properties and heat resistance, but poor transparency, and the majority of the material surface components are polymers, so the hardness is still in the common improvement range of polymer modification, and no substantial breakthrough has been achieved. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology, and to provide a PMMA composite glass material with high hardness and high light transmittance, and a preparation method and application thereof. To solve the above technical problem, the technical solution proposed by the present invention is: a preparation method of a PMMA composite glass material, comprising:
[0006] Providing a liquid matrix material and inorganic glass, wherein the liquid matrix material comprises polymethyl methacrylate, methyl methacrylate, a compound containing a phosphoric acid group, and an initiator;
[0007] Mixing the liquid matrix materials to obtain a homogeneous mixed liquid;
[0008] The homogeneous mixed liquid is placed between two pieces of inorganic glass and heated to cause a polymerization reaction, and the PMMA composite glass material is obtained by polymerization molding; the reaction between the compound containing a phosphoric acid group and the contact surface of the inorganic glass is:
[0009]
[0010] Where n is a positive integer; at most one of R1 and R2 is a hydrogen atom, and the others are C a1 H a2 O a3 P a4 N a5 Group, a1~a5∈[1,18] positive integers.
[0011] In one embodiment, at least one of R1 and R2 contains an olefinic bond and is an unsaturated compound containing a phosphoric acid group, wherein the compound containing a phosphoric acid group includes an unsaturated compound containing a phosphoric acid group, and the reaction of the unsaturated compound containing a phosphoric acid group with methyl methacrylate is:
[0012]
[0013] In one embodiment, the unsaturated phosphate group-containing compound is one or more of the following compounds:
[0014]
[0015] In one embodiment, R1 and R2 do not contain an olefinic bond and are saturated compounds containing phosphoric acid groups, wherein the compounds containing phosphoric acid groups include saturated compounds containing phosphoric acid groups, and the saturated compounds containing phosphoric acid groups are one or more of the following compounds:
[0016]
[0017] In one embodiment, the mass ratio of the polymethyl methacrylate, methyl methacrylate, the compound containing a phosphoric acid group, and the initiator is (5-20): (60-90): (1-20): (0.1-0.5).
[0018] In one embodiment, the homogeneous mixed liquid is placed between two pieces of inorganic glass and heated to react, and the specific steps are:
[0019] A reaction cavity for containing liquid is formed between two pieces of inorganic glass, and the reaction cavity has a pouring port;
[0020] Filling the homogeneous mixed liquid into the reaction cavity from the filling port;
[0021] The reaction cavity is sealed, and polymerization molding is completed through water bath heating and air bath heating. After the reaction is completed, the reaction cavity and the sealing component are removed to obtain a PMMA composite glass material.
[0022] In one embodiment, the water bath heating temperature is 45-65° C., the water bath heating time is 2-10 h, the air bath heating temperature is 100-130° C., and the air bath heating time is 1-5 h.
[0023] In one embodiment, the viscosity of the homogeneous mixture is measured at 25° C. using a Tu-4 cup, and the outflow time is 15 to 150 seconds.
[0024] In one embodiment, before the polymerization molding, the process further includes: soaking the inorganic glass in a strong alkaline solution.
[0025] In one embodiment, the substituent C of the compound containing a phosphate group a1 H a2 O a3 P a4 N a5 It does not contain benzene rings or amide bonds.
[0026] Based on a general inventive concept, the present invention also provides a PMMA composite glass material obtained by the preparation method of the above-mentioned PMMA composite glass material, the PMMA composite glass material includes a first inorganic glass layer, a polymer layer, and a second inorganic glass layer arranged in sequence, and the polymer layer is formed by polymerizing a homogeneous mixed liquid with the contact surfaces of the first inorganic glass layer and the second inorganic glass layer respectively.
[0027] Based on a general inventive concept, the present invention also provides an application of a PMMA composite glass material in aircraft, building curtain walls or rail transportation.
[0028] In summary, compared with the prior art, the beneficial effects of the present invention are as follows: in the PMMA composite glass material of the present invention and the preparation method thereof, the compound containing the phosphoric acid group undergoes a continuous condensation reaction with a large number of silanol groups existing on the contact surface of the inorganic glass to form Si-OP chemical bonding, thereby forming a polymer layer that is difficult to separate from the inorganic glass between the two pieces of inorganic glass, and brute force disassembly will only result in two results: the inorganic glass itself is broken or a thin layer of fragments is partially bitten off by the organic glass, thereby obtaining a PMMA composite glass material with a polymer layer formed between the double layers of inorganic glass, and the surface Mohs hardness of the PMMA composite glass material is greatly improved from 2.5 of ordinary organic glass to 6 (Shore hardness exceeds 99, while the intrinsic Shore hardness of organic glass is only 91), and the hardness of the PMMA composite glass material is significantly improved. At the same time, the refractive index of the PMMA composite glass material of the present invention is very close to that of PMMA, and the transmittance can be as high as over 92%. Therefore, the PMMA composite glass material of the present invention breaks the balance limitation between the hardness and transmittance of the PMMA matrix transparent material, and achieves improved consistency between the two. A new PMMA composite glass material with extremely high wear resistance and reliability can be obtained through the method of the present application.
[0029] The PMMA composite glass material of the present invention has high hardness, high wear resistance and high light transmittance. The PMMA composite glass material can replace the application position of the original inorganic glass, and is particularly suitable for scenes with strong demand for weight reduction, such as aircraft, building curtain walls, rail transportation and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 is a schematic flow chart of a method for preparing a PMMA composite glass material according to an embodiment;
[0032] Figure 2 is a schematic diagram of a molding process of a PMMA composite glass material according to an embodiment;
[0033] Figure 3 is a schematic diagram of a cross-sectional structure of a PMMA composite glass material according to an embodiment;
[0034] Figure 4 This is a photograph of inorganic glass fragmentation caused by forceful disassembly of the PMMA composite glass obtained in Example 3;
[0035] Figure 5 These are photos of different angles and surface hardness tests of the corresponding plates of inorganic glass and organic glass formed by forcefully disassembling the PMMA composite glass obtained in Example 1, wherein a is a schematic diagram of the horizontal plane of the inorganic glass after forcefully disassembling; b is a schematic diagram of the horizontal plane of the organic glass after forcefully disassembling; c is a schematic diagram of the inclined plane of the inorganic glass after forcefully disassembling; d is the inclined plane of the organic glass after forcefully disassembling, wherein the dots are the indentation marks left by the hardness tester during the test, the upper red circle corresponds to the hardness test mark of the inorganic glass fragment surface bitten off by the organic glass, and the lower red circle corresponds to the hardness test mark of the exposed surface of the organic glass; e is the Shore D hardness test value corresponding to the red circle above the inorganic glass fragment in d; f is the Shore D hardness test value corresponding to the red circle below the organic glass fragment in d;
[0036] Figure 6 It is a schematic diagram of the light transmittance results of Examples 1 to 5 and Comparative Example 1 at different wavelengths. DETAILED DESCRIPTION
[0037] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0038] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0039] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0040] See also Figures 1 to 6 , a method for preparing a PMMA composite glass material according to an embodiment of the present invention (the preparation process is shown in Figure 1 ),include:
[0041] S10, providing a liquid matrix material and inorganic glass, wherein the liquid matrix material comprises polymethyl methacrylate, methyl methacrylate, a compound containing a phosphoric acid group, and an initiator.
[0042] Specifically, in one embodiment, the mass ratio of polymethyl methacrylate, methyl methacrylate, the compound containing a phosphoric acid group, and the initiator is (5-20): (60-90): (1-20): (0.1-0.5).
[0043] The phosphoric acid group-containing compound includes an unsaturated phosphoric acid group-containing compound and a saturated phosphoric acid group-containing compound.
[0044] Specifically, the initiator is selected from one of dibenzoyl peroxide (BPO), azobisisobutyronitrile (ABVN) and azobisisobutyronitrile (AIBN).
[0045] Among them, adding polymethyl methacrylate and methyl methacrylate at the same time can shorten the polymerization reaction time, reduce the release of polymerization reaction heat, make heat control more stable, and prevent explosion from occurring easily. The fluidity or viscosity of the liquid matrix material can also be adjusted by the proportion of polymethyl methacrylate.
[0046] Preferably, the substituent C of the compound containing a phosphate group a1 H a2 O a3 P a4 N a5 There is no benzene ring or amide bond in the compound. The benzene ring or amide bond is a sensitive group that is easily affected by ultraviolet light and causes yellowing. When it contains a benzene ring or an amide bond, yellowing is more likely to occur. Therefore, the substituent C of the compound containing the phosphate group a1 H a2 O a3 P a4 N a5 The absence of benzene rings or amide bonds can ensure that the PMMA composite glass material has a more stable long-term high light transmittance.
[0047] Among the compounds containing phosphoric acid groups, the compounds containing unsaturated phosphoric acid groups can participate in the copolymerization reaction of MMA, while the compounds containing saturated phosphoric acid groups do not react with MMA, and both can participate in the condensation reaction on the contact surface with the inorganic glass. The unsaturated phosphoric acid group-containing compound will not only copolymerize with MMA, but also its phosphoric acid group end will form a new Si-OP chemical bond with the contact surface of the inorganic glass, thereby forming a strong bond, so it is a more preferred solution that the compounds containing phosphoric acid groups include unsaturated phosphoric acid group-containing compounds.
[0048] Preferably, the unsaturated compound containing a phosphoric acid group is one or more of the following compounds:
[0049]
[0050] Preferably, the saturated phosphate group-containing compound is one or more of the following compounds:
[0051]
[0052] S20, mixing the liquid matrix materials to obtain a homogeneous mixed liquid.
[0053] Preferably, the viscosity of the homogeneous mixed liquid is measured at 25° C. using a Tu-4 cup, and the outflow time is 15 to 150 seconds. By controlling the viscosity within this range, the subsequent polymerization heat release can be effectively controlled, and the operability during the infusion process is more suitable.
[0054] S30, placing the homogeneous mixed liquid between two pieces of inorganic glass and heating it to cause a polymerization reaction, and obtaining the PMMA composite glass material through polymerization molding; wherein the reaction of the unsaturated compound containing a phosphoric acid group and methyl methacrylate is:
[0055]
[0056] The reaction between the compound containing phosphoric acid group and the contact surface of inorganic glass is:
[0057]
[0058] Where n is a positive integer, at most one of R1 and R2 can be a hydrogen atom and the other can be a C a1 H a2 O a3 P a4 N a5 group, a1~a5∈[1,18] positive integers, at least one of R1 and R2 contains an olefinic bond, then it is an unsaturated compound containing a phosphate group; if neither R1 nor R2 contains an olefinic bond, then it is a saturated compound containing a phosphate group.
[0059] The molding process of the PMMA composite glass material is described in detail in Figure 2 .
[0060] In one implementation, S30 specifically includes:
[0061] S310, forming a reaction cavity for containing liquid between two pieces of inorganic glass, wherein the reaction cavity has a pouring port;
[0062] S320, pouring the homogeneous mixed liquid into the reaction cavity from the pouring inlet;
[0063] S330, sealing the reaction cavity, completing polymerization molding through water bath heating and air bath heating, and removing the reaction cavity and sealing components after the reaction is completed to obtain a PMMA composite glass material. Specifically, the water bath heating temperature is 45-65° C., the water bath heating time is 2-10 hours, the air bath heating temperature is 100-130° C., and the air bath heating time is 1-5 hours.
[0064] Preferably, in one embodiment, before the polymerization molding, the process further comprises: soaking the inorganic glass in a strong alkaline solution, so as to form more hydroxyl groups on the surface of the inorganic glass.
[0065] Among them, if you need to be more familiar with the structure of the reaction cavity, you can refer to the relevant contents in CN213563879U "Polymer casting molding mold", CN214491266U "Fastenin g mechanism of polymer casting mold and polymer casting device", CN214491270U "Mold suitable for rapid casting of polymers", and CN218314761U "A pressure strip assembly and casting device for casting mold".
[0066] The PMMA composite glass material obtained by the above method comprises a first inorganic glass layer 100, a polymer layer 300, a second inorganic glass layer 200 (see Figure 3 ), wherein the first inorganic glass layer 100 and the second inorganic glass layer 200 have the same material and structure. The polymerized layer 300 is formed by polymerizing the homogeneous mixed liquid with the two contact surfaces of the first inorganic glass layer 100 and the second inorganic glass layer 200. The PMMA composite glass material is particularly suitable for application in fields with high transparency and weight reduction requirements, such as aircraft, glass building curtain walls or rail transportation.
[0067] Example 1
[0068] A liquid matrix material and two pieces of inorganic glass of the same shape and size are provided, and the thickness of a single piece of inorganic glass is 2 mm. The compound containing a phosphoric acid group in this embodiment is only a compound containing an unsaturated phosphoric acid group, specifically: 2-acrylic acid-2-hydroxyethyl ester phosphate, and no saturated phosphoric acid group-containing compound is introduced. The initiator is ABVN.
[0069] In the composition of the liquid matrix material, the mass ratio of polymethyl methacrylate, methyl methacrylate, 2-acrylic acid-2-hydroxyethyl ester phosphate, and ABVN is 5:60:1:0.1. The above liquid matrix materials are mixed to obtain a homogeneous mixed liquid, and the viscosity of the homogeneous mixed liquid is measured at 25° C. using a coating-4 cup, and the outflow time is 15 seconds.
[0070] A reaction cavity for holding liquid is formed between two pieces of inorganic glass, the edge of the reaction cavity is sealed with a rubber strip, the thickness of the reaction cavity is 2 mm (controlled by the thickness of the rubber strip), the homogeneous mixed liquid is poured into the reaction cavity and then sealed, placed in a 55°C water bath for continuous heating for 3 hours, and then heated in a 125°C air bath for continuous heating for 2 hours, the reaction cavity and the sealing component (rubber strip) are removed to obtain a PMMA composite glass material. The PMMA composite glass material includes an indisassembled first inorganic glass layer, a polymer layer, and a second inorganic glass layer, with a total thickness of 6 mm.
[0071] Example 2
[0072] Compared with Example 1, the difference is that the compound containing phosphoric acid group in this example is only a compound containing unsaturated phosphoric acid group, specifically: dimethyl vinylphosphonate, and no saturated phosphoric acid group-containing compound is introduced. BPO is selected as the initiator.
[0073] A liquid matrix material and two pieces of inorganic glass with the same shape and size are provided, and the thickness of a single piece of inorganic glass is 3 mm.
[0074] The mass ratio of polymethyl methacrylate, methyl methacrylate, dimethyl vinylphosphonate and initiator is 20:90:20:0.5. The viscosity of the homogeneous mixed liquid obtained by mixing polymethyl methacrylate, methyl methacrylate, dimethyl vinylphosphonate and BPO is measured at 25°C with a coating-4 cup, and the outflow time is 150s. The thickness of the reaction cavity is 3mm, and the others remain unchanged. The total thickness of the PMMA composite glass material obtained is 9mm.
[0075] Example 3
[0076] Compared with Example 1, the difference is that the compounds containing phosphate groups in this example are only compounds containing unsaturated phosphate groups, specifically: bis[2-(methacryloyloxy)ethyl]phosphate and vinyl phosphoric acid, the mass ratio of the two is 8:2 respectively, and no saturated phosphate group-containing compounds are introduced.
[0077] A liquid matrix material and two pieces of inorganic glass having the same shape and size are provided, wherein the thickness of a single piece of inorganic glass is 4 mm.
[0078] The mass ratio of the polymethyl methacrylate, methyl methacrylate, the compound containing a phosphoric acid group, and the initiator is 12:75:10:0.25. The viscosity of the homogeneous mixed liquid obtained by mixing the polymethyl methacrylate, methyl methacrylate, the compound containing a phosphoric acid group, and the initiator is measured at 25°C with a coating-4 cup, and the outflow time is 100s. The thickness of the reaction cavity is 4mm, and the others remain unchanged. The total thickness of the PMMA composite glass material obtained is 12mm.
[0079] Example 4
[0080] Compared with Example 1, the difference is that the compound containing phosphoric acid group in this example is only a compound containing saturated phosphoric acid group, specifically dibutyl phosphate, and no unsaturated phosphoric acid group-containing compound is introduced. AIBN is selected as the initiator.
[0081] A liquid matrix material and two pieces of inorganic glass with the same shape and size are provided, and the thickness of a single piece of inorganic glass is 5 mm.
[0082] The mass fraction ratio of the polymethyl methacrylate, methyl methacrylate, the compound containing a phosphoric acid group, and AIBN is 10:75:5:0.25. The viscosity of the homogeneous mixed liquid obtained by mixing polymethyl methacrylate, methyl methacrylate, the compound containing a phosphoric acid group, and the initiator is measured at 25°C with a coating-4 cup, and the outflow time is 70s. The thickness of the reaction cavity is 5mm, and the others remain unchanged. The total thickness of the PMMA composite glass material obtained is 15mm.
[0083] Example 5
[0084] Compared with Example 1, the difference is that the compound containing a phosphate group in this embodiment contains both a compound of a saturated phosphate group and a compound of an unsaturated phosphate group, specifically: 2-(methacryloyloxy)ethyl-2-(trimethylamino)ethyl phosphate and glycerophosphoric acid, and the mass ratio of the two is 2:8 respectively.
[0085] A liquid matrix material and two pieces of inorganic glass having the same shape and size are provided, wherein the thickness of a single piece of inorganic glass is 6 mm.
[0086] The mass ratio of the polymethyl methacrylate, methyl methacrylate, the compound containing a phosphoric acid group, and the initiator is 15:80:10:0.35. The viscosity of the homogeneous mixed liquid obtained by mixing the polymethyl methacrylate, methyl methacrylate, the compound containing a phosphoric acid group, and the initiator is measured at 25°C with a coating-4 cup, and the outflow time is 50s. The thickness of the reaction cavity is 6mm, and the others remain unchanged. The total thickness of the PMMA composite glass material obtained is 18mm.
[0087] Comparative Example 1
[0088] Consistent with the existing manufacturing technology of ordinary PMMA materials, the thickness of the reaction cavity is 6 mm, and the specific process is not repeated. At this time, the homogeneous mixed liquid poured is composed only of polymethyl methacrylate and methyl methacrylate, and the viscosity is measured at 25°C with a coating-4 cup, and the outflow time is 100s. The type and amount of initiator and the polymerization process are all consistent with Example 1. In this way, the thickness of the ordinary PMMA material obtained under the existing manufacturing technology is 6 mm.
[0089] The surface hardness of the PMMA composite glass materials manufactured in Examples 1 to 5 and the ordinary PMMA material in Comparative Example 1 was tested (the results are shown in Table 1). The samples used in Examples 1 to 5 and Comparative Example 1 were required to meet the standard requirements of the corresponding tests, and the results were averaged. The surface hardness of the above samples was evaluated using a Shore D hardness tester, and the value of 99 reached the limit of the equipment range ( Figure 5e shows that the actual hardness value has exceeded 99, but for record purposes, the hardness data in the table is temporarily collected with 99 as the actual measured value). Since the actual surface of the samples prepared in Examples 1 to 5 is inorganic glass, that is, the specific hardness of the PMMA composite glass material is determined by the inorganic glass itself, that is, the type of inorganic glass and the difference brought about by the molding process will determine the final surface hardness of the material obtained by this technical solution. In contrast, as an ordinary PMMA material, the Shore D of Comparative Example 1 is only 91. In addition to the Shore hardness index, the present application also conducted a Mohs hardness test accordingly. The PMMA composite glass materials manufactured in Examples 1 to 5 all have inorganic glass surfaces, and the Mohs hardness values are all 6, while the surface of Comparative Example 1 is an ordinary PMMA material, and its Mohs hardness is only 2.5.
[0090] Compared with Comparative Example 1, the inorganic glass constituting the cavity reacts with the fully cured PMMA in the cavity to form a chemical bond of Si-OP in the inorganic / organic interface region ( Figure 2 ) and are strongly bonded to form a whole and cannot be disassembled. Therefore, the PMMA composite glass material obtained in Examples 1 to 5 has a cross-sectional structure of an inorganic glass sandwiching a PMMA intermediate layer on the upper and lower surfaces ( Figure 3 ) spatial form. Among them, the inorganic glass sandwiched PMMA middle layer is obtained by removing all auxiliary parts (such as edge clamps) and sealing components (strips) of the reaction cavity after the polymerization reaction is completed, and then using a water jet cutting method to perform vertical cutting. The trajectory is located within the top projection of the original sealing strip at an appropriate distance. Therefore, the PMMA composite glass material finally obtained has a structure consisting of only the upper and lower inorganic glasses and the organic glass compounded between the two.
[0091] The data in Table 1 show that since Examples 1 to 5 form a PMMA composite glass material, the surface hardness is consistent with that of inorganic glass (Shore hardness 99, Mohs hardness 6), and the transmittance of the first two groups is greater than 92%, and the lowest group is also greater than 88%, breaking the balance limit between the hardness and transmittance of the PMMA matrix transparent material, achieving consistency improvement between the two, and obtaining a new PMMA composite glass material with extremely high wear resistance and reliability. In order to intuitively experience the substantial progress of the technical solution in the present invention, Example 3 was selected for destructive testing, and a wooden hard stick was used to forcefully separate the inorganic glass in a corner. Under a sufficiently large force, the inorganic glass eventually exploded, while the organic glass still could not be separated at this time ( Figure 4 ); The PMMA composite glass material of Example 1 was subjected to the same brute force method, but the force application point was changed to force the inorganic glass and the organic glass to separate. Although the inorganic glass did not burst, thin layers of inorganic glass fragments of varying thickness remained on the surface of the organic glass ( Figure 5), indicating that under this technical solution, the bonding force of the inorganic / organic interface is greater than the cohesive force of the inorganic glass itself.
[0092] The transmittance is characterized by UV-Vis spectrum, with a wavelength range of 200 to 1100 nm. The transmittance test in the visible light region is based on GB / T 7134-2008 Casting Industrial Organic Glass Sheet, using the transmittance data at a wavelength of 420 nm. The specific results are shown in Figure 6 As shown in Table 1, the light transmittance of Comparative Example 1 is 92.81%, and the light transmittances of Examples 1 to 5 are 92.57%, 92.55%, 90.28%, 89.77% and 88.72%, respectively. The values of Example 1 and Example 2 are extremely close to those of Comparative Example 1, and the naked eye cannot distinguish the difference in light transmittance of the other groups compared with Comparative Example 1, indicating that the light transmittance of the PMMA composite glass material is highly consistent with that of Comparative Example 1, and the light transmittance is almost not reduced under the condition of greatly increasing the surface hardness.
[0093] Table 1. Performance evaluation table of examples and comparative examples
[0094]
[0095] The thickness of the inorganic glass of the PMMA composite glass material of the present invention can be customized, as long as it can stably withstand the vertical locking force of the clamp during the cavity sealing and the subsequent polymerization stage without breaking. Therefore, in the specific implementation stage, in order to ensure safety, the thickness of the inorganic glass should be greater than 1mm, but this does not exclude the range of thickness less than 1mm from the protection scope of the present invention, because the way of providing the locking force is one of the important factors that cause the inorganic glass to break. For example, under the elastic contact surface, the safety will be further improved and the risk of breakage will be lower. In addition, the thickness of the polymerization layer in the PMMA composite glass material of the present invention is determined by the thickness of the reaction cavity, while the overall format is controlled by the external dimensions of the reaction cavity. The thickness of the PMMA composite glass material of the present invention is greater than or equal to 2mm, and the format size can be freely selected according to actual needs, so it is easy to achieve customized production.
[0096] The PMMA composite glass material obtained by the method of the present invention has the following unique technical advantages:
[0097] 1. Ultra-high hardness. The results of using brute force to separate the layers of the PMMA composite glass material of the present invention are: the inorganic glass is broken (untempered) or exploded (tempered, such as Figure 4 ), or part of the inorganic glass is "bitten off" by the organic glass and remains on the surface of the organic glass (such as Figure 5), which fully demonstrates that the inorganic / organic interface bonding force exceeds the cohesive force of the inorganic glass itself, and the Shore hardness is as high as 99 or above (the surface Mohs hardness is greatly improved from 2.5 to 6), which is extremely rare in the field of organic glass manufacturing and modification. The surface hardness of the composite material is exactly the same as that of inorganic glass, and it can almost withstand most application requirements in the industrial field. In the field with transparent and high wear resistance requirements, it can play a unique role. Common, such as rail transit noise control (the sound barrier is exposed to dust for a long time, and the surface of the PMMA sheet under the existing technology is prone to scratches. Especially in arid areas, the adverse effects of wind and sand are more significant). The technical solution of this application is adopted, and the surface smoothness can still be effectively maintained after long-term use.
[0098] 2. Excellent fireproof performance. The polymer layer of the PMMA composite glass material of the present invention contains compounds containing phosphoric acid groups in different amounts. Since phosphorus has an ideal flame retardant effect and is non-halogen and has excellent environmental protection performance, the obtained polymer layer has certain flame retardant performance. Combined with the non-combustible properties of the inorganic glass on the upper and lower surfaces, the composite material has ideal overall fireproof properties and can be used in fields with high fireproofing requirements such as interior decoration and building materials.
[0099] 3. Lower overall density. Compared with inorganic glass of the same thickness, the PMMA composite glass material of the present invention has a lower density and has a certain range of free adjustment space. It is used in the aviation field with strong demands for transparency and weight reduction, such as transparent parts in the cockpit of civil airliners or other aircraft (the key priority of air vehicles is material weight reduction. Compared with the use of all inorganic glass materials, the PMMA composite glass material of the present invention not only retains the high surface hardness and high wear resistance of inorganic glass, but also can achieve effective weight reduction, which can well meet such weight-sensitive and lightweight application scenarios).
[0100] 4. Since the refractive index of inorganic glass is very similar to that of PMMA, both are around 1.50, the PMMA composite glass material obtained can have an excellent transmittance of up to 92%, breaking the balance limit between the hardness and transmittance of the PMMA transparent material matrix, achieving improved consistency between the two, and obtaining a transparent organic glass composite material with high wear resistance and reliability.
[0101] 5. By adjusting the structural dimensions of the cavity, such as the thickness or outer diameter of the rubber strip, the overall width, etc., it is possible to obtain a PMMA composite glass material with customized thickness, length and width of the inorganic glass layer and the polymer layer. It has a highly flexible control space and can better meet the differentiated needs of the market.
[0102] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing a PMMA composite glass material, characterized in that: include: Providing a liquid matrix material and inorganic glass, wherein the liquid matrix material comprises polymethyl methacrylate, methyl methacrylate, a compound containing a phosphoric acid group, and an initiator; Mixing the liquid matrix materials to obtain a homogeneous mixed liquid; The homogeneous mixed liquid is placed between two pieces of inorganic glass and heated to cause a polymerization reaction, and the PMMA composite glass material is obtained by polymerization molding; the reaction between the compound containing a phosphoric acid group and the contact surface of the inorganic glass is: Where n is a positive integer; at most one of R1 and R2 is a hydrogen atom, and the others are C a1 H a2 O a3 P a4 N a5 Group, a1~a5∈[1,18] positive integers.
2. The method for preparing the PMMA composite glass material according to claim 1, characterized in that: At least one of R1 and R2 contains an olefinic bond and is an unsaturated compound containing a phosphoric acid group, wherein the compound containing a phosphoric acid group includes an unsaturated compound containing a phosphoric acid group, and the reaction of the unsaturated compound containing a phosphoric acid group with methyl methacrylate is:
3. The method for preparing the PMMA composite glass material according to claim 2, characterized in that: The unsaturated compound containing a phosphoric acid group is one or more of the following compounds:
4. The method for preparing the PMMA composite glass material according to claim 1, characterized in that: If neither R1 nor R2 contains an olefinic bond, the compound is a saturated phosphoric acid group-containing compound, wherein the phosphoric acid group-containing compound includes a saturated phosphoric acid group-containing compound, and the saturated phosphoric acid group-containing compound is one or more of the following compounds:
5. The method for preparing the PMMA composite glass material according to claim 1, characterized in that: The mass ratio of the polymethyl methacrylate, methyl methacrylate, the compound containing a phosphoric acid group, and the initiator is (5-20): (60-90): (1-20): (0.1-0.5).
6. The method for preparing the PMMA composite glass material according to claim 1, characterized in that: The homogeneous mixed liquid is placed between two pieces of inorganic glass and heated to react, and the specific steps are as follows: A reaction cavity for containing liquid is formed between two pieces of inorganic glass, and the reaction cavity has a pouring port; Filling the homogeneous mixed liquid into the reaction cavity from the filling port; The reaction cavity is sealed, and polymerization molding is completed through water bath heating and air bath heating. After the reaction is completed, the reaction cavity and the sealing component are removed to obtain a PMMA composite glass material.
7. The method for preparing the PMMA composite glass material according to claim 6, characterized in that: The water bath heating temperature is 45-65°C, the water bath heating time is 2-10 hours, the air bath heating temperature is 100-130°C, and the air bath heating time is 1-5 hours.
8. The method for preparing the PMMA composite glass material according to claim 1, characterized in that: The viscosity of the homogeneous mixed liquid is measured at 25° C. using a Tu-4 cup, and the outflow time is 15 to 150 seconds.
9. The method for preparing the PMMA composite glass material according to claim 1, characterized in that: Before the polymerization molding, the method also includes: soaking the inorganic glass in a strong alkaline solution.
10. The method for preparing the PMMA composite glass material according to claim 1, characterized in that: Substituent C of compounds containing phosphate groups a1 H a2 O a3 P a4 N a5 It does not contain benzene rings or amide bonds.
11. A PMMA composite glass material obtained by the preparation method of the PMMA composite glass material according to any one of claims 1 to 10, characterized in that: The PMMA composite glass material comprises a first inorganic glass layer, a polymer layer and a second inorganic glass layer arranged in sequence, wherein the polymer layer is formed by polymerizing a homogeneous mixed liquid with contact surfaces of the first inorganic glass layer and the second inorganic glass layer respectively.
12. Use of the PMMA composite glass material according to claim 11 in aircraft, building curtain walls or rail transportation.
Citation Information
Patent Citations
Glass-imitation polymer composite material and preparation method thereof
CN110218433A
Resin-based material and preparation method of surface hardening layer of composite material of resin-based material
CN117229555A
Macromolecule casting forming mold
CN213563879U
Fastening mechanism of macromolecule pouring mold and macromolecule pouring device
CN214491266U
Mould suitable for fast pouring of macromolecules
CN214491270U